ANTIMICROBIAL ACTIVITY OF MINERAL TRIOXIDE AGGREGATE AND CALCIUM HYDROXIDE SEALER ON ENTEROCOCCUS FAECALIS STRAIN ATCC29212 - PRATHITA, TARA; DJAUHARIE, NILA KESUMA; MEIDYAWATI, RATNA (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this study was to evaluate the antimicrobial activity of mineral trioxide aggregate (MTA) and calcium hydroxide (Ca(OH)2) sealers on Enterococcus faecalis at various time points after the preparation of the sealer. Methods: Antimicrobial activity of MTA and Ca(OH)2 sealer on E. faecalis (ATCC 29212) was assessed by the direct contact test immediately, 1 day, and 7 days after the preparation of the sealer. Results: The antimicrobial effect of MTA sealer was greatest 1 and 7 days after the preparation of the sealer. The effect of Ca(OH)2 was greatest 1 day after the preparation of the sealer. Conclusion: MTA sealer showed constant antimicrobial activity on E. faecalis overtime. By contrast, Ca(OH)2 sealer showed decreasing antimicrobial activity overtime, with the greatest antimicrobial activity being 1 day after the preparation of the sealer.